THE EFFECTIVENESS OF THE CEFE TRAINING MODEL TO IMPROVE UMKM INDEPENDENCE IN CIMAHI CITY, WEST JAVA PROVINCE - Ade Sadikin Akhyadi; Nike Kamarubiani; Jajat S. Ardiwinata; Cucu Sukmana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
This study aims to provide a study by describing the effectiveness of CEFE training management in perfecting an entrepreneurship training program. The research method applied is a qualitative approach with an Emic view, then data collection involves MSME actors, assistants, and coordinators as well as data collection tools with observation, documentation, interviews, and tests. Based on the results of the study, it was found that the management of the CEFE training was very helpful in training management and specifically to deal with problems in the business world, then based on the discussion carried out, the management of the training model was more structured and focused when compared to not implementing the training model. This management applies real simulations to the entrepreneurial world which makes this model very suitable to be applied to entrepreneurship training programs. The impact of this research is to create insight into employment opportunities, increase entrepreneurial insight and create a family spirit, and train participants to develop businesses through business partners